2019
DOI: 10.31983/jrg.v7i2.5150
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Konseling Gizi Dengan Media Booklet Terhadap Konsumsi Sayur Buah Dan Fast Food Pada Remaja Obesitas

Abstract: Background: Several factors cause obesity in adolescence are the lack of consumption of vegetables, fruits and excessive consumption of fast food. Nutrition counseling about benefits of vegetables, fruits and the impact of fast food on obesity is an effort that would be increase consumption of vegetables, fruits and reduce consumption of fast food.Objective: To determine the effect of counseling with booklet media on consumption of vegetables, fruits and fast food in obese adolescents at SMP N 40 Semarang.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
1
Order By: Relevance
“…nutrition (p = 0.74) between the control and intervention groups. Meanwhile, the Mann Whitney test on the difference in the mean portion of fruit consumption showed that there was a significant difference between the control group and the intervention group (p = 0.01) 17 .…”
Section: Resultsmentioning
confidence: 96%
“…nutrition (p = 0.74) between the control and intervention groups. Meanwhile, the Mann Whitney test on the difference in the mean portion of fruit consumption showed that there was a significant difference between the control group and the intervention group (p = 0.01) 17 .…”
Section: Resultsmentioning
confidence: 96%
“…Konseling tentu menggunakan media sebagai alat dukung keberhasilan program. Konseling akan terlaksana secara baik jika memanfaatkan media seperti booklet, sehingga klien lebih mudah dalam memahami masalah gizi dan kesehatan (Ningrum et al, 2019).…”
Section: Pendahuluanunclassified
“…Thus, if the basic concept given is wrong, it will carry over to adulthood. In this phase, development is influenced by the environment [17], [18]. For this reason, low-grade elementary school children need attention and guidance, especially from various parties, including parents, schools, and teachers, mainly to prevent bullying deviant behaviour.…”
Section: Introductionmentioning
confidence: 99%